2017
DOI: 10.1007/s00436-017-5603-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Enterocytozoon bieneusi isolates in laboratory macaques in north China: zoonotic concerns

Abstract: The significance of wild and zoo nonhuman primates (NHPs) as potential sources of human Enterocytozoon bieneusi infections has been increasingly appreciated, while the role of laboratory NHPs in zoonotic transmission of microsporidiosis remains elusive. In this study, the infection rate, genetic characteristic, and zoonotic potential of E. bieneusi were investigated for 205 laboratory macaques in Beijing, north China. The parasite was identified in 37 (18.0%) animals by nested PCR and sequencing of the ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
2
9
2
Order By: Relevance
“…In the present study, the most prevalent genotype was D which has also been found in captive non-human primates, domestic rabbits, captive foxes, captive raccoon dogs, pet chinchillas, and many other captive wildlife ( Karim et al, 2014a ; Du et al, 2015 ; Qi et al, 2015 ; Yang et al, 2015 , 2016 , 2017 ; Zhao et al, 2015 ; Li et al, 2016b ; Xu et al, 2016 ; Zhang et al, 2016a , b ; Yu et al, 2017 ). In addition, the second most prevalent genotype was EbpC which was also more frequently found in some captive animals (captive foxes and captive non-human primates) ( Karim et al, 2014a ; Zhao et al, 2015 ; Yang et al, 2017 ); however, Peru11 was only found in captive non-human primates in China ( Karim et al, 2014a ; Yang et al, 2017 ). These findings also suggested that these genotypes of E. bieneusi might transmission among these captive animals.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the most prevalent genotype was D which has also been found in captive non-human primates, domestic rabbits, captive foxes, captive raccoon dogs, pet chinchillas, and many other captive wildlife ( Karim et al, 2014a ; Du et al, 2015 ; Qi et al, 2015 ; Yang et al, 2015 , 2016 , 2017 ; Zhao et al, 2015 ; Li et al, 2016b ; Xu et al, 2016 ; Zhang et al, 2016a , b ; Yu et al, 2017 ). In addition, the second most prevalent genotype was EbpC which was also more frequently found in some captive animals (captive foxes and captive non-human primates) ( Karim et al, 2014a ; Zhao et al, 2015 ; Yang et al, 2017 ); however, Peru11 was only found in captive non-human primates in China ( Karim et al, 2014a ; Yang et al, 2017 ). These findings also suggested that these genotypes of E. bieneusi might transmission among these captive animals.…”
Section: Discussionsupporting
confidence: 64%
“…Since the detection of E. bieneusi in AIDS patients in 1985 for the first time, this pathogen has been found in other immunocompromised/immunodeficient individuals, such as organ transplant recipients, children, and lifethreatening and persistent diarrhea often occur in these populations [2][3][4][5][6][7]. It has been recently identified in several species of non-human primates (NHPs) in China and elsewhere [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ITS genotypes in Group 1 and Group 2 have been found in a broad range of hosts including humans and are probably responsible for most zoonotic or cross-species E. bieneusi infections whereas host adaptation seems to be more common in genotypes of Groups 3 to 11 according to a recent review of E. bieneusi [6]. To date, more than 100 E. bieneusi genotypes have been detected in NHPs, mostly belonging to Group 1 [6,9,10,13,14,[17][18][19][20][21]. Among them, Type IV and Peru8 are common ITS genotypes in humans and various animals in many countries, including China [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous reports, genotype D (synonymous with genotypes PigEBITS9, WL8, Peru9, CEbC, PTEb VI) were identified in many mammals including human, reptile and birds ( Da Cunha et al, 2017 ; Huang et al, 2019 ). The reports of genotype CM1 (synonymous with genotype Macaque3) was less, it was only found in NHPs and dog at present ( Karim et al, 2014a , 2014b , 2015 ; Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 87%
“…However, higher infection rate of 31.1% (33/106) was reported in six zoos in eastern China ( Karim et al, 2015 ). In Beijing Rhesus macaque laboratory, the infection rate of E. bieneusi in cynomolgus monkeys was 25.6% while in Rhesus macaques was only 4.2% (3/72) ( Yang et al, 2017 ). The reasons for the differences in infection rates may be related to the environmental conditions of different populations, the health of the animals at the time of sampling and the overall sample size.…”
Section: Discussionmentioning
confidence: 99%